Pengembangan dan validasi modul konseling pasca bencana untuk konselor - Ifdil Ifdil; Faizah Abd Ghani (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2017)
This research objective to: (1) describe the design of Module counseling postdisaster (2) perform the module validity test and (3) perform the module reliability test. This study is a descriptive study involving 4 experts and 12 counselors from several areas in West Sumatra as the subject of trials. Instrument used includes (1) instrument validity content of module (2) Inventory training knowledge improvement counseling service for post disaster (3) Inventory of proficiency of post disaster counseling service (4) reliability module instrument (5) training session instrument. The result of this study reveals the post-disease counseling module can be accepted and can be used for self awareness program, knowledge and counselor competence in doing conscience post disaster event. It is expected that this module can be used by counselors and developed by advanced researchers.